2015
DOI: 10.1016/j.jacep.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Thrombogenic Risk in Patients With Atrial Fibrillation

Abstract: Patients with lone AF and those with AF and comorbidities had a greater propensity for atrial thrombogenesis than controls. Prothrombotic risk is greatest in those with comorbid conditions, in whom enhanced thrombogenesis occurs predominantly through increase in endothelial dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…This may be attributed to the higher proportion of CHF, HTN, female sex, higher age and DM that are proven to accompany LVH. 11) 12) 13) 14) 15) 16) Increased LV mass impairs the LV diastolic function and elevates the LV end-diastolic pressure (LVEDP) as shown in the increasing values of LVMI, LAVI and E/E′ in Table 2 and Figure 2 . These data suggest that a higher number of clinical attributes favorable of stroke collectively result in impaired diastolic function but not systolic functions.…”
Section: Discussionmentioning
confidence: 96%
“…This may be attributed to the higher proportion of CHF, HTN, female sex, higher age and DM that are proven to accompany LVH. 11) 12) 13) 14) 15) 16) Increased LV mass impairs the LV diastolic function and elevates the LV end-diastolic pressure (LVEDP) as shown in the increasing values of LVMI, LAVI and E/E′ in Table 2 and Figure 2 . These data suggest that a higher number of clinical attributes favorable of stroke collectively result in impaired diastolic function but not systolic functions.…”
Section: Discussionmentioning
confidence: 96%
“…Stamboul et al [169] reported higher ADMA levels in patients who developed AF after myocardial infarction. A stepwise increase of ADMA concentrations has been shown in controls, in patients with lone AF and in patients with AF and other comorbidities [170]. This notion fostered further investigation relating ADMA and SDMA to permanent rather than paroxysmal AF in acute ischemic stroke [171].…”
Section: Cardioembolic Stroke and Embolic Stroke Of Undetermined Sourcementioning
confidence: 93%
“…Cardiovascular risk factors, cardiovascular comorbidities, and AF burden trigger, maintain, and accelerate hemostasis activation [32][33][34][35][36][37][38][39][40]. TF has been reported to be a central initiator and mediator of endothelial activation [36][37][38][39][40][41][42].…”
Section: Plasma Biomarkers Indicate a Prothrombotic And Hypercoagulab...mentioning
confidence: 99%
“…AF (even in the absence of structural heart disease, hypertension, diabetes mellitus, coronary artery disease, or a history of stroke), cardiovascular risk factors, and cardiovascular disease (in the absence of AF) all result in the inflammatory activation of the endothelial layer [32,33]. This phenomenon can be observed locally (LA) and systemically.…”
Section: Plasma Biomarkers Indicate a Prothrombotic And Hypercoagulab...mentioning
confidence: 99%
See 1 more Smart Citation